Nursing Facility and Health Care Service Use and Costs Under the CMS Financial Alignment Initiative. (17th December 2021) - Palmer, Lauren; Toth, Matt; Wang, Joyce; Schneider, Emily; Dorneo, Allison; Chiri, Giuseppina; Walsh, Edith
Abstract: The Centers for Medicare & Medicaid Services created the Financial Alignment Initiative (FAI) to test the impact of integrated care and financing models for dually eligible Medicare-Medicaid beneficiaries. Using Medicare claims, the Minimum Data Set 3.0, and state-provided enrollment files, we evaluated demonstration impacts on long-stay nursing facility (NF) use, other health care service utilization, and costs for the overall eligible population in two FAI demonstration States with managed fee-for-service models, Colorado and Washington. We used quasi-experimental, difference-in-differences regression models for the impact analyses. In Colorado, there was a 7.2 percent decrease (p<0.001) in long-stay NF use, relative to the comparison group. Otherwise, the demonstration showed unfavorable service utilization results—increases in preventable emergency department (ED) visits and declines in 30-day follow-up after mental health discharge (MHFU)—and no impact on Medicare costs. In Washington, there was also a decrease in long-stay NF use (12.4 percent, p<0.001) and skilled NF admissions (21.7 percent, p<0.001). However, the demonstration resulted in decreases in physician visits and 30-day MHFU. There was a favorable decrease in Medicare costs. The impact of the FAI demonstrations on NF use was favorable for both States, while the impact on service utilization and Medicare costs was mixed and more favorable in Washington. Washington's care coordination model was intensive and targeted to high-cost individuals while Colorado provided minimal care coordination. Coordinated care and integrated long-term services and support may help postpone NF institutionalization, but there is no evidence these activities reduced preventable hospitalizations or ED visits.